Patient use of complementary and alternative medicine for psoriasis vulgaris and factors believed to trigger the disease: A multicenter cross-sectional study with 1621 patients - Aslan Kayıran, Melek; Karadağ, Ayşe Serap; Topal, İlteriş Oğuz; Emre, Selma; Adışen, Esra; Kılıç, Sevilay; Keskin, Nuray; Kara Polat, Asude; Çevirgen Cemil, Bengü; Polat, Mualla; Yılmaz, Oğuz; Ayvaz, Hilal; et al. (Mattioli 1885, 2022)
Introduction: Due to the chronic recurrent nature of psoriasis vulgaris (PV) and lack of definitive treatment for the disease, patients often resort to alternative treatments. Physicians seem to have low awareness of this issue. Objectives: To elicit the perceptions of 1,621 PV patients on complementary and alternative medicine (CAM) and examine factors reported to worsen PV. Methods: The patients sociodemographic characteristics, Psoriasis Area Severity Index (PASI), Dermatology Life Quality Index (DLQI), disease duration, and severity were recorded, and the patients CAM use was questioned in detail. The patients were also asked about factors that worsened PV and their experiences with a gluten-free diet. Results: Of the patients, 56.51% had used CAM. The mean age, illness duration, PASI scores and DLQI of those using CAM were significantly higher. CAM use was significantly higher in those with facial, genital involvement, and arthralgia/arthritis. The patients mostly referred to CAM when PV became severe (46.4%). Of the CAM users, 45.52% used herbal topicals. The physicians of 67.03% did not inquire whether they used CAM. Of the participants, 37.73% considered that stress worsened their disease. Gluten-free diet did not affect PV symptoms in 52.22%. Conclusions: Patients CAM use is often overlooked by dermatologists. Our results showed that more than half the patients used CAM and did not share this information with their physicians. Therefore, the awareness of physicians should be increased and patients should be asked about the use of CAM and directed to the appropriate medical treatment options by physicians.
Keywords: Psoriasis Vulgaris; Complementary and Alternative Medicine; Diet; Gluten; Stress